Twin reversed arterial perfusion syndrome (TRAP or acardiac twin) in pregnancy: a case report - I Nyoman Hariyasa Sanjaya; Cokorda Istri Mirayani Pemayun; Ni Luh Made Diah Mas Cahyani Putri; Ni Wayan Dewi Purwanti; Made Diah Vendita Sakuntari; Ni Putu Nining Gianni; Ni Komang Anik Pirgantari; Ni Luh Md Dwi Laxmi Satriani; Firsta Sesarina Mintariani; Anak Agung Wahyu Putri Agustini; Ketut Widyani Astuti (Indonesian Journal of Perinatology, 2022)
Introduction: A type of pregnancy that occurs in monochorionic twin pregnancies which results in the coexistence of normal "pump" twins and cardiac twins is called Twin Reverse Arterial Perfusion Syndrome (TRAP). The low oxygen pressure going to the baby causes many unique changes in the twins' physiology. These changes can lead to high prenatal mortality. Case Presentation: We present the case of a 25-year-old woman, primigravida, whose obstetrician referred to Kasih Medika Bali with suspicion of a large placenta. However, upon arrival at 35 weeks and 2 days of gestation, an ultrasound showed a twin pregnancy with suspicion of a TRAP pregnancy. Then, a baby girl was born at Payangan Hospital, Gianyar, Bali by Sectio Caesarea with a birth weight of 3155 grams, an Apgar score of 6-8-9, and a placental weight of 815 grams. The results of the examination of the second fetus that did not develop, weighing 1,705 grams in the placenta did not have an attached umbilical cord. The doctor's suspicions about the TRAP pregnancy were indeed true according to the conditions at the time of the twins' birth. The doctor found 1 healthy baby and 1 other like mass with a size large enough on ultrasound at 35 weeks 2 days of gestation. Conclusion: The incidence of pregnancy like this is very rare and needs further study in order to detect early abnormalities that occur in pregnancy. Thus, we can be aware of the risks for both mother and fetus and even treat them early. Couples can be counseled optimistically that the recurrence rate of TRAP syndrome tends to be low so that they can better plan future pregnancies in all aspects.